Vagus Nerve Stimulation as a Potential Adjuvant to Rehabilitation for Post-stroke Motor Speech Disorders - Morrison, Robert A.; Hays, Seth A.; Kilgard, Michael P. (Frontiers in Neuroscience, 2021)
Stroke often leaves lasting impairments affecting orofacial function. While speech therapy is able to enhance function after stroke, many patients see only modest improvements after treatment. This partial restoration of function after rehabilitation suggests that there is a need for further intervention. Rehabilitative strategies that augment the effects of traditional speech therapy hold promise to yield greater efficacy and reduce disability associated with motor speech disorders. Recent studies demonstrate that brief bursts of vagus nerve stimulation (VNS) can facilitate the benefits of rehabilitative interventions. VNS paired with upper limb rehabilitation enhances recovery of upper limb function in patients with chronic stroke. Animal studies reveal that these improvements are driven by VNS-dependent synaptic plasticity in motor networks. Moreover, preclinical evidence demonstrates that a similar strategy of pairing VNS can promote synaptic reorganization in orofacial networks. Building on these findings, we postulate that VNS-directed orofacial plasticity could target post-stroke motor speech disorders. Here, we outline the rationale for pairing VNS with traditional speech therapy to enhance recovery in the context of stroke of speech motor function. We also explore similar treatments that aim to enhance synaptic plasticity during speech therapy, and how VNS differs from these existing therapeutic strategies. Based on this evidence, we posit that VNS-paired speech therapy shows promise as a means of enhancing recovery after post-stroke motor speech disorders. Continued development is necessary to comprehensively establish and optimize this approach, which has the potential to increase quality of life for the many individuals suffering with these common impairments.